2016
DOI: 10.1186/s12885-016-2613-6
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and cost-utility of a guided self-help exercise program for patients treated with total laryngectomy: protocol of a multi-center randomized controlled trial

Abstract: BackgroundTotal laryngectomy with or without adjuvant (chemo)radiation often induces speech, swallowing and neck and shoulder problems. Speech, swallowing and shoulder exercises may prevent or diminish these problems. The aim of the present paper is to describe the study, which is designed to investigate the effectiveness and cost-utility of a guided self-help exercise program built into the application “In Tune without Cords” among patients treated with total laryngectomy.Methods/designPatients, up to 5 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…A previous study suggested that a patient support network may help solve swallowing problems using a patient-to-patient communication model [17]. Then, a clinical study was carried out to evaluate the effectiveness and cost-utility of a guided self-help exercise program among patients treated by total laryngectomy [29]. Long-term studies involving this patient population are also needed as it has been suggested that even the patients who successfully recover swallowing after function-preserving laryngeal surgery may lose this function later; indeed, patients present with aspiration 11–15 years after partial laryngectomy and require definitive total laryngectomy [30].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study suggested that a patient support network may help solve swallowing problems using a patient-to-patient communication model [17]. Then, a clinical study was carried out to evaluate the effectiveness and cost-utility of a guided self-help exercise program among patients treated by total laryngectomy [29]. Long-term studies involving this patient population are also needed as it has been suggested that even the patients who successfully recover swallowing after function-preserving laryngeal surgery may lose this function later; indeed, patients present with aspiration 11–15 years after partial laryngectomy and require definitive total laryngectomy [30].…”
Section: Discussionmentioning
confidence: 99%
“…Further research should investigate whether patient activation can be improved in cancer patients, and whether this affects health status and total costs. A currently ongoing Dutch randomized controlled trial on the (cost-)effectiveness of a guided self-help program in TL cancer patients may provide further information regarding this association [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous systematic review of Panagioti et al [ 15 ] indeed found that self-management interventions for different populations with chronic illnesses may reduce healthcare utilization without compromising patients’ health outcomes. In cancer patients specifically, only few studies focused on the impact of self-management interventions on (healthcare) costs so far, although several researchers are planning to [ 8 10 ]. A recent study comparing psychologist-led care with a nurse-led self-management intervention in distressed cancer patients showed no evidence for cost-effectiveness of the self-management intervention [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that improvement of HRQOL is possible for every cancer survivor, regardless of having a low or high HRQOL at the start of the intervention, and the benefit of Oncokompas might be through reducing symptom burden. Evidence on moderating effects of baseline values of HRQOL is inconsistent [5,42].…”
Section: Discussionmentioning
confidence: 99%